Principles of Cell Biology - George Plopper (Jones & Bartlett, 2016)
Each new print copy includes Navigate 2 Advantage Access that unlocks a comprehensive and interactive eBook, student practice activities and assessments, a full suite of instructor resources, and learning analytics reporting tools. Written for undergraduate cell biology courses, Principles of Cell Biology, Second Edition provides students with the formula for understanding the fundamental concepts of cell biology. This practical text focuses on the underlying principles that illustrate both how cells function as well as how we study them. It identifies 10 specific principles of cell biology and devotes a separate chapter to illustrate each. The result is a shift away from the traditional focus on technical details and towards a more integrative view of cellular activity that is flexible and can be tailored to suit students with a broad range of backgrounds. The Second Edition features a fully revised art program with new full-color images and illustrations that simplify key concepts and cell function. Concept Check questions at the end of each section along with new end-of-chapter questions assess student comprehension, ensuring retention of key cell biology principles. An informal, narrative writing style makes even the most complex concepts accessible to students new to the scientific field, making Principles of Cell Biology the clear choice for anyone studying the fascinating field of cell biology